Multifunctional Role of the Whey Culture Medium in the Spray Drying Microencapsulation of Lactic Acid Bacteria - Stephania Aragón-Rojas; María Ximena Quintanilla-Carvajal; Humberto Hernández-Sánchez (Food Technology and Biotechnology, 2018)
This study aims to evaluate the multifunctional role of whey culture medium during the spray drying microencapsulation of Lactobacillus fermentum K73. Whey culture medium containing growing microorganisms served to hydrate different mixtures (gum arabic, maltodextrin and whey). We evaluated the use of these mixtures as carbon sources and their protective effects on simulated gastrointestinal conditions. The optimal mixture was spray-dried while varying the outlet temperature and atomizing pressure using a response surface design. These conditions served to evaluate microorganism survival, tolerance to gastrointestinal conditions in vitro, physicochemical properties, morphometric features and stability at 4, 25 and 37 °C. Lactobacillus fermentum K73 replicated in the carrier material. Bacterial change cycles were (–1.97±0.16) log CFU/g after the drying process and (–0.61±0.08) and (–0.23±0.00) log CFU/g after exposure of the capsules to simulated gastric pH and bile salt content, respectively. The physicochemical properties and morphometric features were within the normal ranges for a powder product. The powder was stable at a storage temperature of 4 °C. The spray drying of the whey culture medium with growing microorganisms using the optimized drying conditions was successful. This study demonstrates the use of whey culture medium as a component of carrier material or as the carrier material itself, as well as its protective effects during drying, under simulated gastrointestinal conditions, and at varied storage temperatures.